2016
DOI: 10.3171/2015.4.jns141257
|View full text |Cite
|
Sign up to set email alerts
|

Results of delayed follow-up imaging in traumatic brain injury

Abstract: OBJECT There is a paucity of scientific evidence available about the benefits of outpatient follow-up imaging for traumatic brain injury patients. In this study, 1 year of consecutive patients at a Level 1 trauma center were analyzed to determine if there is any benefit to routinely obtaining CT of the head at the outpatient follow-up visit. METHODS This single-institution retrospective review was performed on all patients with a traumatic brain injury seen at a Level 1 trauma center in 2013. Demographic data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Several studies using urodynamics on TBI patients have reported up to 85% of patients with bladder dysfunction 57,58 . Moreover, this dysfunction can persist longer term as reported by Khan et al (2016) where 34% of the group studied had combined bladder and bowel issues up to 5 years after a brain injury 59,60 . Bladder dysfunction that remains after rehabilitation contributes to a higher risk factor for a patient to be re-institutionalized 61 .…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…Several studies using urodynamics on TBI patients have reported up to 85% of patients with bladder dysfunction 57,58 . Moreover, this dysfunction can persist longer term as reported by Khan et al (2016) where 34% of the group studied had combined bladder and bowel issues up to 5 years after a brain injury 59,60 . Bladder dysfunction that remains after rehabilitation contributes to a higher risk factor for a patient to be re-institutionalized 61 .…”
mentioning
confidence: 74%
“…By contrast, TBI is relatively common and leads to clear cut brain degeneration. Models incorporating rmdTBI lead to brain degeneration which models human TBI as seen in collision sports or military trauma, with well characterized loss of cognitive and motor function and, in our studies, with loss of normal bladder function [6][7][8][9][10][11]20,54,[59][60][61] .…”
Section: Discussionmentioning
confidence: 99%